Joint coordination when running in minimalist, neutral, and ultra-cushioning shoes - Borgia, B.; Freedman Silvernail, J.; Becker, J. (Journal of Sports Sciences, 2020)
Ultra-cushioning (ULTRA) shoes are new to the running shoe market. Several studies have evaluated kinematics and kinetics while running in ULTRA shoes, however it remains unknown how such shoes influence joint coordination. Therefore, the purpose of this study was to evaluate lower extremity coordination and coordination variability when running in minimalist (MIN), traditional (NEUT) and ULTRA shoes. Fifteen runners ran for ten minutes in each shoe type. Coordination patterns and coordination variability were assessed for rearfoot-tibia, rearfoot-knee, and tibia-knee couplings using a modified vector coding method during early, mid, and late stance periods. During late stance ULTRA shoes resulted in more antiphase coordination than MIN (p =.036) or NEUT (p =.047) shoes and less in-phase coordination than MIN (p =.048) or NEUT (p =.013) shoes. During late stance there was also more proximal phase rearfoot-knee coordination in ULTRA shoes than in either MIN (p =.039) or NEUT (p =.005) shoes and less in-phase coordination in ULTRA shoes than in NEUT shoes (p =.006). There were no differences in coordination variability between shoes during any phase. The differences in coordination may have implications for tissue loading and injury development when running in ULTRA shoes.